Sources of Directional Spatial Biases in Hemi-Image Drawing. (February 2020) - Garcia, Omar; Faghihi, Nafiseh; Vaid, Jyotsna
We examined the performance of right- and left-handed brain-intact adult readers of English or Farsi on a hemi-image generation task in which participants were to imagine and then draw halves of objects using either their dominant or nondominant hand. Which half of the object was drawn was examined in relation to biomechanical, cerebral laterality, and cultural predictors. Findings showed a differential side bias as a function of reading/writing direction and hand used to draw. Specifically, when the dominant hand was used to draw (Experiment 1), English left-handers produced more left hemi-images while Farsi right-handers produced more right hemi-images. Body specificity associated with hand used, however, drove spatial preference when enlisting the nondominant hand (Experiment 2) with English right-handers now showing a significant left hemi-image bias and English left-handers showing a right hemi-image bias. Farsi right-handers using their nondominant hand did not show a significant bias in either direction. Taken together, the findings suggest a joint influence of handedness and reading/writing direction, aligned with an embodiment account of directional spatial biases.